Gender distinctiveness, communicative competence, and the problem of gender judgments in computer-mediated communication - Sierpe, Eino (Computers in Human Behavior, 2005)
Despite persistent claims regarding the ability of text-based computer-mediated communication to neutralize gender identities, few researchers have worked on the problem of gender distinctiveness in textual production and interpretation, gender judgments, and more importantly, the role of gender in the process of impression formation in electronic communication. Against this background, the author addresses the theoretical aspects of gender in textual communication and places the problem of gender distinctiveness and gender judgments in CIVIC in the context of Hymes' model of communicative competence. He also isolates several variables worthy of investigation, namely, the provision of gender judgments, accuracy, and certainty. He then reconceptualizes the problem of gender distinctiveness and impression formation in CIVIC by bridging the gap between textual markedness and expectations. (C) 2003 Elsevier Ltd. All rights reserved.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/055-557-328-035-914 tex.type: [object Object]
Keywords: Communicative competence; Computer-mediated communication; Electronic communications; Formal languages; Gender judgments; Linguistics; Problem solving; Research; dept.ils; peer-reviewed